Realizing the Well-Being of Senior Citizen by Developing Smart Application: A Conceptual Model - Nasution, Ammar Ihsan; Ibrahim, Jamaludin (Faculty of Computer Science (FILKOM) Brawijaya University, 2021)
Years after years, there is an increased number of senior citizens in Malaysia. As the result, senior citizens become one of the society segments that given a priority focus by the government. Many programmes are planned by the government to help the senior citizen. But, issues on senior citizen still occurred, such as financial/economy, social, emotion/psychology, religious spiritual, education/knowledge, health, environment, family, and others. Today, technology grows rapidly and used in many sectors, including education, health, security, and in daily activities. Harnessing technology makesÂ life easier and productive. Mobile application can be found easily and utilized by everyone. The researcher believes that this technology/smart application can help the senior citizen to be productive and have a good life. Literature Review, Business Model Environment Map (EM), Business Model Canvas (BMC), and Value Preposition Canvas (VPC) used as the method of this paper. Therefore, this research paper proposed a conceptual solution to realize the well-being of Senior citizen through Smart Application.